Chloroplast and nuclear DNA studies in Iberian Peninsula endemic Silene scabriflora subspecies using cpSSR and ISSR markers: Genetic diversity and phylogenetic relationships. (August 2015) - Ferreira, Vanessa; Castro, Isaura; Rocha, João; Crespí, António L.; Pinto-Carnide, Olinda; Amich, Francisco; Almeida, Rubim; Carnide, Valdemar
Abstract: The Iberian Peninsula is considered to be a center of natural distribution and diversity for several species of flora. In this study, the genetic diversity and phylogenetic relationships of Silene scabriflora from the Iberian Peninsula were analyzed using ISSR and cpSSR markers. A total of 161 ISSR markers were produced, with a percentage of polymorphic loci of 99.4%. A high level of genetic differentiation among S. scabriflora subspecies ( S. scabriflora spp. scabriflora, S. scabriflora spp. megacalycina, S. scabriflora spp. gallaecica and S. scabriflora spp. tuberculata ) was observed (Gst = 0.3685), which was illustrated by UPGMA dendrogram. Molecular results are in agreement with subspecies morphological characterization, particularly supporting the morphological similarities between S. scabriflora spp. scabriflora and S. scabriflora spp. megacalycina . Three of the five cpSSR loci analyzed were polymorphic and the two different alleles found in each polymorphic locus were combined in two different haplotypes. The results obtained in this study provide evidences for a long distance dispersion theory, Southern of Spain as the biodiversity center of S. scabriflora ; for speciation, Southern of Spain as a refugia-within-refugia considering the speciation that occurs in S. scabriflora spp. scabriflora found in this region and the possibility of S. scabriflora spp. scabriflora as being ancestral of the species. Highlights: First study involving Silene scabriflora subspecies endemic from Iberian Peninsula using ISSRs and cpSSRs. First attempt to uncover genetic differentiation and relationships among S. scabriflora subspecies. Geography, environment and glacial refugia may be the factors generating variation among subspecies.